Study on the needs of tuna fish as raw material for macro scale fish processing industry in Banda Aceh. Issue 1 (November 2021) - Muhammad, M; Maulana, R; Rizwan, T; Chaliluddin, M. A.; Zulfahmi, I; Saputra,; Suhendrianto,
Abstract: Aceh Province has a great potential fish resource, sustainable Potential on Capture Fisheries about 272, 707 tons and total Capture Fishery Production is 208, 200, 830, moreover this potential has not been utilized optimally. The cached Fish at Koetaradja Fishing Port Banda Aceh are still abundant, so it is possible to be proceed industrially either at micro or macro scale. This study aims to examine the needs of the fishing industry in Aceh Province about the need of fish raw materials and to find out the type and amount of raw materials needed by a fish processing industry (macro scale) in Banda Aceh city. In addition, interviews and questionnaires were used as the instruments in collecting data. This research was conducted to five macro-scale fishery processing companies in Banda Aceh City there are PT. Aceh Samudera Bahari, PT. Aceh Lampulo Jaya Bahari, CV. Thunnus Saputra, PT. Sure Tuna Pacific and CV. Barakah Sumber Bahari. The results showed that there were 3 types of fish used as the processed raw materials, there are skipjack, tuna and kite fish. Skipjack tuna is the most fish needed by every processed industry. The need for fish raw materials at PT. Aceh Samudera Bahari requires skipjack tuna raw materials about 58, 098 Kg/month (697, 176 Kg/year), At PT. Aceh Lampulo Jaya Bahari requires the raw materials for skipjack tuna about 25, 972 Kg/month (311, 664 Kg/year, PT. Yakin Tuna Pasifik requires raw materials for skipjack tuna about 52, 788 Kg/month (633, 456 Kg/year), and CV. Barakah Sumber Bahari requires 20, 498 Kg/month of skipjack fish raw materials (245, 976 Kg/year). The total of all skipjack tuna raw materials needed by these 5 companies in one year is 3, 205, 224 Kg.